Deciding who is the best. Validity issues in selections and judgements in elite sport - Johansson, A. (Department of Education, Umea University, 2010)
This thesis is about selection processes and processes of measuring and judging athletes in competitions in top-level sport. The purpose was to increase the knowledge of these processes and to analyse them from a validity perspective in order to contribute to the discussion of whether the "right" athletes are selected to participate in teams, competitions and games and whether the "right" athletes win. The rule and judging systems were investigated in the judged sports acroski and rhythmic gymnastics. Information was gathered through individual interviews with two judges, two coaches, and four elite athletes from each of the sports, and in addition to this the respective sport`s rule systems, judging manuals, meeting protocols and historical documents were studied. Selections to top-level sport teams were investigated by individual interviews with 14 top-level coaches (selectors) from the national league in soccer and a national team and from national teams in alpine skiing. The results from the judging study showed that both studied sports had undergone major changes in their rule and judging regulations, changes that had a considerable impact on the sports and the judgements. The level of definition of the rules and regulations was raised to increase the opportunities for clear and reliable judgements, but this became problematic for the overall validity of the judgements. The reason for this was that the new rules and regulations did not clearly correspond to the original idea of the sport, since the specified and detailed regulations lead to less originality and freedom in the performances. In the selection study, the results pointed to great differences in how precisely defined the selection criteria were among the teams. The selectors stated that well-defined selection criteria or grounds could be helpful in many ways, but they also emphasised how important it was for them that some parts of the selections were based on their subjective valuations of the athletes. Quite a few coaches from both sports argued that they would choose an athlete with good behaviour and favourable personality over an athlete with better sports skills, if they had an opportunity to do that depending on the selection system that was used. Overall, this research displays how validity issues connected to the selection and judging criteria and these processes might affect the outcome of the processes. It is notable that high reliability is in the main focus of the measuring and judging processes, while considerably vaguer and more subjective assessments are considered important in the selection process. The thesis points to the importance of discussing and understanding the consequences of rules, rule changes, selection and judging criteria as well as how these processes are performed, if the desired outcomes and consequences of the selection and judging processes are to be reached.